Individual, social and physical environmental correlates of children's active free-play: a cross-sectional study - Ball Kylie; Salmon Jo; Veitch Jenny (BMC, 2010)
Abstract Background Children's unstructured outdoor free-play (or active free-play) has the potential to make an important contribution to children's overall physical activity levels. Limited research has, however, examined physical activity in this domain. This study examined associations between individual, social and physical environmental factors and the frequency with which children play in particular outdoor locations outside school hours. This study also investigated whether the frequency of playing in outdoor locations was associated with children's overall physical activity levels. Methods Participants including 8-9 year old children and their parents (n = 187) were recruited from a selection of primary schools of varying socioeconomic status across metropolitan Melbourne, Australia. Parents completed a survey and children's overall physical activity levels were measured by accelerometry. Regression models examined the odds of children playing in various outdoor settings according to particular correlates. Results Inverse associations were found between preference for activities not involving physical activity, and the likelihood of children playing in the yard at home on the weekend (OR = 0.65; CI = 0.45,0.95). Positive correlates of children playing in their own street included: parental perceptions that it was safe for their child to play in their street (weekdays [OR = 6.46; CI = 2.84,14.71], weekend days [OR = 6.01; CI = 2.68,13.47]); children having many friends in their neighbourhood (OR = 2.63; CI = 1.21,5.76); and living in a cul-de-sac (weekdays [OR = 3.99; CI = 1.65,9.66], weekend days [OR = 3.49; CI = 1.49,8.16]). Positive correlates of more frequent play in the park/playground on weekdays included family going to the park together on a weekly basis on weekdays (OR = 6.8; CI = 3.4,13.6); and on weekend days (OR = 7.36; CI = 3.6,15.0). No differences in mean mins/day of moderate-vigorous physical activity were found between children in the highest and lowest tertiles for frequency of playing in particular outdoor locations. Conclusion The presence of friends, safety issues and aspects of the built environment were reported by parents to be associated with children's active free-play in outdoor locations. Future research needs to further examine associations with time spent in active free-play and objectively-measured overall physical activity levels. It is also important to investigate strategies for developing a supportive social and physical environment that provides opportunities for children to engage in active free-play.